Effect of bicycle saddle designs on the pressure to the perineum of the bicyclist - Lowe, B. D.; Schrader, S. M.; Breitenstein, M. J. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: Increasing awareness of an association between bicycling and male sexual dysfunction has led to the appearance of a variety of bicycle saddles that share the design objective of reducing pressure in the groin of the cyclist by removal of the narrow protruding nose of the saddle. This study compared three of these saddle designs to a traditional sport/road racing saddle with a narrow protruding nose in terms of pressure in the region of the perineum (groin) of the cyclist. METHODS: Saddle, pedal, and handlebar contact pressure were measured from 33 bicycle police patrol officers pedaling a stationary bicycle at a controlled cadence and workload. Pressure was characterized over the saddle as a whole and over a region of the saddle assumed to represent pressure on the cyclist's perineum located anteriorly to the ischial tuberosities. RESULTS: The traditional sport/racing saddle was associated with more than two times the pressure in the perineal region than the saddles without a protruding nose (P < 0.01). There were no significant differences in perineal pressure among the nontraditional saddles. Measures of load on the pedals and handlebars indicated no differences between the traditional saddle and those without protruding noses. This finding is contradictory to those studies suggesting a shift toward greater weight distribution on the handlebars and pedals when using a saddle without a nose. CONCLUSIONS: The recommendation of a saddle without a narrow protruding nose appears to be justified to reduce pressure to the perineum of the bicyclist.